ROR1 as a Therapeutic Target In E2A-PBX1-Positive Acute Lymphoblastic Leukemia - Bicocca, Vincent; Chang, Bill H; Muschen, Markus; Druker, Brian J; Tyner, Jeffrey W (Blood, 2010)
Abstract 539 Aberrant tyrosine kinase activity is commonly implicated in the pathogenesis of leukemia and other cancers. Identification of these leukemogenic tyrosine kinases has proven invaluable for diagnostic and prognostic stratification of patients as well as for the development of novel strategies for therapeutic intervention. We previously demonstrated that siRNA screening of mononuclear cells from leukemia patients can determine sensitivity to individual tyrosine kinases. With the goal of uncovering novel viability-dependent tyrosine kinases in leukemia patients, we have employed an RNAi-assisted protein target identification (RAPID) assay to screen cytogenetic subtypes of acute lymphoblastic leukemia (ALL). ALL is the most common pediatric cancer, accounting for one-quarter of all childhood malignancies. Childhood ALL has a primarily B cell precursor phenotype and is characterized by chromosomal abnormalities, primarily translocations and duplications. These lesions can result in aberrant tyrosine kinase expression and activity required for leukemogenesis. One of the most common recurring translocations associated with pediatric ALL, t(1;19)(q23;p13.3), generates the E2A-PBX1 fusion product. The role of E2A-PBX1 in the development of acute leukemia remains unclear. Here we show unique viability-dependent expression of a receptor tyrosine kinase, ROR1, in the E2A-PBX1 ALL background. In addition, we identify a kinase inhibitor, dasatinib, with significant activity against E2A-PBX1-positive ALL cells. To identify targets required for viability of leukemic cells, we screened cell lines as well as primary cells from ALL patients by electroporating siRNAs individually targeting each member of the tyrosine kinase gene family. Four days later, we determined the cell viability and tabulated sensitivity of the cells to any individual tyrosine kinase. ROR1 expression levels were determined by RT-PCR, immunoblot analysis and flow cytometry. Kinase inhibitor screening was performed on both cell lines and primary ALL cells by treating samples with a library of small-molecule inhibitors consisting of 90 cell-permeable inhibitor compounds. Inhibitors are plated at four serial dilutions to allow IC50 calculations. The effect of each drug on cell viability is determined at day three by an MTS cell viability assay. The RAPID assay identified a unique sensitivity to the receptor tyrosine kinase-like orphan receptor 1 (ROR1) in a subject identified with E2A-PBX1-positive B cell precursor pediatric ALL. Similar sensitivity was not observed in patients of other leukemic backgrounds or ALL patients of alternative cytogenetic subtypes. Examination of mononuclear cells from this patient by reverse-transcriptase-PCR revealed overexpression of the ROR1 transcript compared with ALL patients lacking the E2A-PBX1 fusion product. Examination of 12 additional E2A-PBX1-positive ALL patient samples revealed universal overexpression of ROR1 within the E2A-PBX1 background. Analysis of E2A-PBX1-positive cell lines and early passage xenograft cells showed both overexpression of ROR1 and sensitivity to siRNA-mediated ROR1 silencing, confirming the ROR1 dependent survival observed in primary cells with the RAPID assay. Finally, since ROR1 is defined as a tyrosine kinase, we performed a kinase inhibitor screen and identified universal sensitivity of E2A-PBX1-positive cell lines and patient samples to the FDA-approved drug dasatinib. Hence, dasatinib is suggested as a potential therapeutic for E2A-PBX1-positive ALL patients. The cell surface receptor ROR1 is consistently overexpressed in E2A-PBX1-positive ALL. RNAi mediated downregulation of ROR1 impairs the viability of these cells. Finally, the kinase inhibitor dasatinib is suggested as a novel therapeutic tool for treatment of E2A-PBX1-positive ALL based on universal sensitivity of E2A-PBX1 samples to this kinase inhibitor. Druker:Molecular MD: Equity Ownership.